INSTITUTIONAL FOUNDATIONS OF POLAND’S ACCESSION TO THE EUROPEAN UNION - Zalesko, Marian (Ekonomia i Prawo. Economics and Law, 2012)
Research on economic integration constitutes a significant position in the scientific literature. The process of consolidation of the economies, particularly in Europe, as an expansion of the European Union, is the essence of a debate between representatives from the various social sciences, especially economists. This article focuses on Poland’s preparations for accession into the European Union. The analysis was performed from a historical perspective, using the tools of institutional economics.